Deregulacja rynku pracy jako instrument polityki państwa na rynku pracy - Puzio-Wacławik, Bogusława (Labour Market Deregulation as an Instrument of a Country's Policy in the Labour Market, 2009)
In the article, the author tackles the problem of the deregulation policy in the labour market. The first part presents the situation of the elasticity in labour markets in European countries and information on the implementation of this strategy. Next, the article describes the situation in Poland, conditions and possibilities of using elastic forms of employment according to the Polish labour code. In the end, the author draws conclusions from the situation in the labour market in Poland and too little information on profits from the labour market deregulation for its participants.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 345-353